COMPARATIVE EVALUATION OF POLYHERBAL COMBINATION FOR HYPOLIPIDEMIC ACTIVITY (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Hyperlipidemia is defined as increase in the lipid content (group of fat or fat like substances along with their lipoprotein counterpart) in blood. The present study was undertaken to explore the antihyperlipidemic effect of ethanolic extract from Fenugreek and Gymnema sylvestre and hydro-alcoholic extract from Curcuma longa in cholesterol diet induced hyperlipidemia in rats. Oral administration of various extracts once in a day for two weeks significantly lowered the total cholesterol phospholipid, triglycerides, low density lipoproteins and increase the high density lipoprotein level. Present investigation shows that Curcumin caused more significant decrease in the total cholesterol level (1.36 %), serum level of triglyceride (1.32 %), and serum level of LDL (1.39 %) as compared to other groups in cholesterol diet induced hyperlipidemia and atherosclerosis. The study exhibited that elevated blood cholesterol; triglycerides, LDL, and decrease HDL which occur in Hyperlipidemia were significantly reduced by the administration of combination of Curcumin, Gymnema sylvestre and Fenugreek.